Safety recommendations for dentists and maxillofacial surgeons during COVID-19 pandemic - Sadat, SM Anwar; Shaikh, Mushfiq H; Attygalla, Manjula; Rao, Naman R; Nagao, Toru; Warnakulasuriya, Saman; Rita, Sufia Nasrin (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Oral health professionals are at high risk of developing COVID-19 infection due to their practice of close proximity to the patients. Patients in daily dental practice can be seen with basic protection protocol. Routine and elective dental procedures should be cancelled during this pandemic situation and could be rescheduled when the situation eases. In practice, as of universal prevention strategy, all patients should be assumed as COVID-19 infected and treated accordingly. Adequate standards of hygiene and protection should be adopted for all patients to avoid potential transmission risks. During the COVID-19 pandemic, it would be crucial to categorize oral and maxillofacial surgery cases into: emergency case, urgent case, intermediate case and low priority cases. While there has been a growing literature suggesting the aspect of critical care associated in treating these patients, ample of evidence indicates how this COVID-19 pandemic will affect surgical practice. Here we highlight the current unfavorable situation due to COVID -19 and offer recommendations for changes to dental and maxillofacial surgical practices. J Bangladesh Coll Phys Surg 2020; 38(4): 197-204